Impact of genetic diseases on anthropometric parameters – A case–control study - Suvarna Magar; Anjali Kale; Shrushti Agarwal; Pranoti Toshniwal (Indian Journal of Child Health, 2021)
Background: It is observed that anthropometric parameters are lower in children suffering from genetic diseases as compared to other children. The WHO growth charts help us to get information if the anthropometric parameters are below or above 3 standard deviations (SD) but getting exact SD, can diagnose different etiologies and mechanisms of underlying growth faltering much precisely. Objectives: The objectives of the study were to calculate the exact SD of anthropometric parameters in cases with genetic diseases and to compare the SDs with the age- and sex-matched controls to find the impact of same on genetic diagnoses. Materials and Methods: This study was done in tertiary care center of Maharashtra. Cases (n=47) were defined as children with global developmental delay (GDD) (age 3 months–5 years) referred to the genetic clinic. Controls (n=47) were children with normal developmental milestones admitted in pediatric ward for community-acquired infections or illnesses. Results: There was a statistically significant lower mean weight ([8.3 vs. 10.4 kg]; p<0.05) and length ([74.7 vs. 82.5 cm]; p<0.001) and head circumference (HC) ([43.2 vs. 46.07 cm]; p<0.05), among children with developmental delay. The exact SD was calculated based on the “anthropometric calculator” digital mobile app based on the WHO growth charts. It revealed that means of SD for weight, height, and HC in both GDD and normal development of children were –2.9, –3.2, and –2.6 and –1.01, –0.84, and –0.64, respectively. Conclusion: Measuring the anthropometric parameters and interpreting growth and development are an important step in evaluation of a patient but identifying exact SDs of anthropometric measurements are a vital step for getting the genetic clues.